Measuring the effects of structural reforms in Malta: an analysis using the EAGLE model - Brian Micallef (Central Bank of Malta, 2013)
It is widely recognised that structural reforms are needed to boost long-term growth potential and increase an economy's flexibility to adjust in the face of shocks. This paper quantifies the macroeconomic effects of structural reforms in services and labour markets using the EAGLE model calibrated for the Maltese economy. EAGLE is a large scale, multi-country dynamic general equilibrium model. The results show that a 10 percentage point reduction in services and labour mark-ups raises GDP by more than 5% in the long-run. The impact of labour market reforms is more pronounced than that of services reform. If implemented in isolation, however, both reforms are associated with adjustment costs. On the contrary, the joint implementation of reforms can soften, to a large extent, the transition costs associated with pursuing the reforms in isolation. An important driver behind these results is the adjustment in the labour market. This calls for policies to reduce mismatches between the demand and supply of skills that are required in today's industries and to provide incentives so that more people are attracted and retained in the labour market.
Keywords: C53; E27; F41; F47; 330